2020
DOI: 10.1055/a-1171-1865
|View full text |Cite
|
Sign up to set email alerts
|

Workload Monitoring in Top-level Soccer Players During Congested Fixture Periods

Abstract: This study assessed the internal and external workload of starters and non-starters in a professional top-level soccer team during a congested fixture period. Twenty Serie A soccer players were monitored in this study during two mesocycles of 21 days each. Starters and non-starters were divided based on the match time played in each mesocycle. The following metrics were recorded: exposure time, total distance, relative total distance, high-speed running distance over 20 km·h−1, very high-speed running distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 12 publications
(27 reference statements)
0
69
0
1
Order By: Relevance
“…Moreover, it has been reported that the sole training sessions planned during a microcycle may fail to replicate the match equivalent HSR and sprinting load [4,22,34,36]. As a consequence, the lack of HSR and sprinting exposure and the missing adequate physiological stimuli, may likely preclude an effective soccer-specific conditioning process, particularly in non-starter players [22,36]. Therefore, soccer coaches should implement different training methods in the days following a match by considering individual players' match time exposure (e. g. starters vs non-starters) for an effective management of HSR and sprinting training [36].…”
Section: Evidence-based Hsr and Sprinting Conditioning Methodologies mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has been reported that the sole training sessions planned during a microcycle may fail to replicate the match equivalent HSR and sprinting load [4,22,34,36]. As a consequence, the lack of HSR and sprinting exposure and the missing adequate physiological stimuli, may likely preclude an effective soccer-specific conditioning process, particularly in non-starter players [22,36]. Therefore, soccer coaches should implement different training methods in the days following a match by considering individual players' match time exposure (e. g. starters vs non-starters) for an effective management of HSR and sprinting training [36].…”
Section: Evidence-based Hsr and Sprinting Conditioning Methodologies mentioning
confidence: 99%
“…Therefore, soccer coaches should implement different training methods in the days following a match by considering individual players' match time exposure (e. g. starters vs non-starters) for an effective management of HSR and sprinting training [36]. Alternatively, during congested fixture periods in which the available training time is limited, practitioners may consider to plan dedicated training sessions for non-starters immediately after the match conclusion when logistically feasible [22].…”
Section: Evidence-based Hsr and Sprinting Conditioning Methodologies mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently a study concluded that nonstarters (i.e., substitutes who played) had a lower internal and external load, considering matches and training sessions, during congested schedules [ 30 ], confirming that matches are a crucial training component (i.e., substitutes might be detrained). Allowing soccer to increase substitutions permanently across the games, would potentially be a “game changer”.…”
Section: Discussionmentioning
confidence: 99%